Behaviour of laying curve in Babcock-380 brown commercial layers in Kelantan, Malaysia - Md. Ruhul Amin; Siti Aisyah Nawawi (2013)
Commercial layers start laying at 18-20 weeks of age and continues until 72 weeks under cost-effective operation. Age of the hens, mortality rate, feed and environmental conditions determine the persistency of production as reflected in the laying curve. In this experiment laying performance of 10000 hen-housed Babcock-380 brown commercial layers housed in Kelantan, Malaysia was assessed in mathematical model using hen-house and hen-day measurements. It revealed that hens reached at peak lay at 21 weeks of age and maintained a stability until 44 weeks. Birds egg laying performance gradually declined with progress in age till 80 weeks. Y= 35176.99 – 397.374 A + 5.065 F gave the best fitted regression line (adj R² = 0.905) for hen-housed egg production per week (A=age of hens in week and F= Kg feed consumed/day). A 87.5% of the total variation in hen-housed egg production could be explained only by age of hens but when feed consumption was added in the model age and feed consumption together explained 90.5% variability. For every week advancement in hen’s age (week) a decrease of 0.039 eggs/hen/day was predicted (adj R² = 83.8%). In this 10000 hen-housed flock mortality/culling averaged at 14.82/week.